PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA ANIMASI TERHADAP AKTIVITAS DAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDI SANGING-SANGING - Sitti Nuraenun Ilahi; Baharullah; Andi Husniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aimed to examine the influence of the Problem-Based Learning (PBL) model assisted by animation media on the learning activities and mathematics learning outcomes of fifth-grade students at SDI Sanging-Sarnging The research method used was a quasi-experimental approach with a non-equivalent group design The population of this study included all fifth-grade students at SDI Sanging-Sanging, with a sample of 25 students from class VA and 25 students from class VB. Data collection was carried out through learning activity questionnaires, learning outcome tests, and documentation. The collected data were analyzed quantitatively using descriptive and inferential statistics. The results of the descriptive statistical analysis showed that the average score for mathematics learning activities in the first experimental class was 78.88 while in the second experimental class was 51.88. The average score for student learning outcomes in the first experimental class was 83.88, and in the second experimental class was 63.12. Meanwhile, the inferential statistical analysis shows that the sig value for student learning activities was 0.000 0.05, with a t-value> t- table, namely 10.567 > 1.676. The sig, value for student learning outcomes was 0.000 <0.05, with a t-value of 10.3671.676. Furthermore, the MANOVA test showed a sig value of 0.000 0.05. This means that there is influence of applying the problem- based learning model assisted by animation media on the leaming activities and mathematics learning outcomes of fifth-grade students at SDI Sanging-Sanging.